Development of Identity in CHARGE Syndrome—A Case Study “I Know Who I Am” - Wanka, Andrea (Frontiers in Education, 2020)
professionals that provide support and service. A review of the literature demonstrates that the vast majority of research regarding CHARGE Syndrome focuses on the medical, developmental and family structures. However, identity research shifts the paradigm to the individual and their unique personality, which encourages professionals to apply their support or services to the human being rather than the disability. This study introduces a method with which it was possible to collect differentiated data from individuals with CHARGE Syndrome themselves through a guided creation of pictorial collages and a specialized interview technique based on their collages. The methodological approach used in this study included structured interviews embedded within the Collage Life Story Elicitation Technique (Van Schalkwyk, 2010). The CLET (Collage Life Story Elicitation Technique) is a protocol to support individuals in their efforts to create their own life story. Analysis of the resulting data was viewed according to several theoretical frameworks applied to the core narrations and the resources. This provided different avenues to the construction of meaning that formed an understanding of identity from the voices of individual themselves. This research initiative uses a single case study of a young man: Janosch. It becomes clear that Janosch does not associate his core identity with CHARGE Syndrome but rather from alternate origins of self. Janosch demonstrated through this research process that the relevance of animals and the topic of tolerance take a leading role in the formation of his identity. Furthermore and unexpected, Janosch’s participation in the Mangas community serves as a primary source of social and emotional support, forms his construction of “togetherness” and strongly influences his concept of the relevance of family. This is in contrast to the role in which friends often impact these components of ones’ own identity. The specialized methodology used in this study demonstrates that individuals with CHARGE Syndrome can be active participants in identity research that realize rich and accurate data.